KOMUNIKASI VIRTUAL MAHASISWA DALAM PERKULIAHAN NON TATAP MUKA: (Studi pada mahasiswa KPI IAIN Curup) - Sari Apriyanti; Robby Aditya Putra; Anrial Anrial (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The spread of the Covid-19 virus resulted in social restrictions being imposed until all teaching and learning processes were hampered, through online learning students can learn as usual and will not miss lecture material, and more flexible time. This research was conducted with a descriptive survey research method, the sample in this study was KPI IAIN Curup students. Data collection techniques using interviews and questionnaires. The results showed that the location of students for online lectures from 32 students as many as 78.1% who answered at home, 21.9% answered at the home of a family/neighbor who had a good internet network. When asked to students the extent to which the material delivered through online lectures, 43.8% of students answered can be understood, 3.1% of students answered very understood, 43.8% of students answered sometimes understood and 9.4% of students answered not understood. 68.8% of students choose face-to-face lectures and 31.2% of students choose online lectures. The results showed that there were still many students who had difficulties due to internet network problems and not all material could be absorbed easily as when lecturers explained in class face to face.